The histone deacetylase inhibitor, sodium butyrate, exhibits neuroprotective effects for ischemic stroke in middle-aged female rats. Issue 1 (December 2016) - Park, Min; Sohrabji, Farida
Abstract Background Sodium butyrate (NaB) is a histone deacetylase (HDAC) inhibitor exhibiting anti-inflammatory and neuroprotective effects in a rat ischemic model of stroke as well as a myocardial ischemia model. Although clinical evidence shows that older women are at higher risk for stroke occurrence and greater stroke severity, no studies have evaluated the effectiveness of NaB either in females or in older animals. Methods To determine the effects of NaB on stroke in older females, acyclic middle-aged Sprague-Dawley female rats (9–11 months old, constant diestrus) were subject to middle cerebral artery occlusion (MCAo) by intracerebral injection of recombinant endothelin-1. Rats were treated with NaB (300 mg/kg, i.p.) at 6 and 30 h following ET-1 injection. Animals were sacrificed at the early (2 days) or late (5 days) acute phase after MCAo. Serum and tissue lysates were collected for biochemical analyses. Results NaB treatment reduced infarct volume and ameliorated sensory motor impairment in middle-aged female rats, when measured at 2 and 5 days post MCAo. At the early acute phase (2 days post stroke), NaB treatment decreased brain lipid peroxides, and reduced serum levels of GFAP, a surrogate marker of blood-brain barrier (BBB) permeability. NaB also reduced expression of the inflammatory cytokine IL-1beta in circulation and IL-18 in the ischemic hemisphere. At the late acute phase (5 days post stroke), NaB treatment further suppressed MCAo-induced increase of IL-1beta, IL-17A, and IL-18 in brain lysates (cortex and striatum) from the ischemic hemisphere, and decreased ischemia-induced upregulation of IL-1beta and IL-18 in circulation, indicating a potent anti-inflammatory effect of the HDAC inhibitor. Moreover, NaB treatment also increased expression of IGF-1, a known neuroprotectant, in peripheral tissue including serum, liver, and spleen at the late acute phase. Conclusions These data provide the first evidence that delayed (>6 h) NaB treatment post-stroke is neuroprotective in older female rats. Additionally, these data also show that in addition to its well-known anti-inflammatory actions, NaB may exert a biphasic effect after stroke, operating initially to reduce BBB permeability and oxidative stress in the brain, and later, elevating IGF-1 expression in peripheral tissues.